The Timing and Source of Long-Run Returns Following Repurchases - Bargeron, Leonce; Bonaime, Alice; Thomas, Shawn (Journal of Financial and Quantitative Analysis, 2017)
This paper investigates the timing and source of anomalous positive long-run abnormal returns following repurchase authorizations. Returns between program authorization and completion announcements are indistinguishable from 0. Abnormal returns occur only after completion announcements. Long-run returns are largely attributable to announcement returns at subsequent authorizations and takeover attempts; that is, anomalous post-authorization returns are not persistent drifts but rather step functions. These findings have important implications for prior papers examining this most persistent and widespread anomaly. Further, our results serve to refocus the search for a rational explanation for the anomaly on subsequent repurchase announcements and takeover bids.